Variabilidade espacial da resistência do solo à penetração e do teor de água em sistema de plantio direto na cultura da soja - Marasca, Indiamara [UNESP]; Alves de Oliveira, Carlos Alberto; Guimaraes, Ednaldo Carvalho; Arantes Rodrigues da Cunha, Joao Paulo; de Assis, Renato Lara; Perin, Adriano; Silva Menezes, Luiz Antonio (Universidade Federal de Uberlândia (UFU), 2011)
A harmful and limiting factor regarding culture productivity is soil compaction, a parameter that can be quantified by the resistance of the soil to penetration and highly influenced by water content. These variables present spatial and temporary variability, characteristics which can be determined by the geostatistical technique. In the light of the above, the present work had as its objective the study of spatial variability of soil resistance to penetration (RP) and water content in the soil (U) in soy culture. The RP values at depths of 0,00-0,10; 0,11-0,20 and 0,21-0,30 m varied from 2,9 to 4,28 MPa and are considered harmful to the root development of legumes, although they have not influenced soy productivity which was 3887 kg ha(-1). The medium water content of the soil was between 0,210 and 0,213 kg kg(-1) for the three depths studied. The resistance of the soil to penetration, expressed through semivariograms, presented spatial dependence at all depths, being adjusted to the spherical model at depths of 0,00-0,10m and exponential at depths of 0,110,20 and 0,21-0,30 m. The spatial variability for all studied layers presented a range of about 20m. The water content in the soil did not present spatial dependence for the depths, presenting randomized distribution.

Um fator prejudicial e limitante à produtividade das culturas é a compactação do solo, parâmetro que pode ser quantificado pela resistência do solo à penetração e altamente influenciado pelo teor de água. Estas variáveis apresentam variabilidade espacial e temporal, características que podem ser determinadas pela técnica de geoestatística. Diante do exposto, o presente trabalho teve como objetivo estudar a variabilidade espacial da resistência do solo à penetração (RP) e do teor de água no solo (U) na cultura da soja. Os valores de RP nas profundidades de 0,00-0,10; 0,11-0,20 e 0,21-0,30 m variaram de 2,9 a 4,28 MPa e são considerados prejudiciais ao desenvolvimento radicular de leguminosas, embora não tenham influenciado a produtividade da soja que foi de 3887 kg ha-1. O teor médio de água do solo ficou entre 0,210 e 0,213 kg kg-1 para as três profundidades estudadas. A resistência do solo à penetração, expressa por meio dos semivariogramas, apresentou dependência espacial em todas as profundidades, ajustando-se ao modelo esférico na profundidade de 0,00-0,10 m e exponencial nas profundidades de 0,11-0,20 e 0,21-0,30 m. A variabilidade espacial para todas as camadas estudadas apresentaram um alcance em torno de 20 m. O teor de água no solo não apresentou dependência espacial para as profundidades, apresentando distribuição aleatória.
Spatial variability of soil resistance to the penetration and content of water in direct planting system of the soy
Keywords: Precision agriculture; Geostatistics; Soil compacting